Versatile poly(3, 4‐ethylenedioxythiophene) poly(styrenesulfonate) films on polydimethylsiloxane substrates having random micro ridges: Study of resistive behaviors of a polymer–polymer laminate. Issue 1 (31st July 2014) - Mehdi, Murtuza; Cho, Kyung Ho; Choi, Kyung Hyun
ABSTRACT Conductive polymers such as poly(3, 4‐ethylenedioxythiophene) poly(styrenesulfonate) or PEDOT:PSS has become increasingly important in present day organic electronics. PEDOT:PSS being a polymer is more durable than metals used in electronics and thus offers greater mechanical flexibility during operation. This article presents results regarding resistive behaviors of blade coated PEDOT:PSS films on polydimethylsiloxane (PDMS) substrate having random micro ridges as a function of axial strain and different temperatures. The average resistance of the blade coated PEDOT:PSS films were found to increase by 1.4 times between 35 and 45% axial strain. The resistances of the films were found to change within the temperature range of 25–230°C without any thermal morphological degradations and the polymer–polymer laminate also showed linear thermal actuation behavior. These results suggest that the blade coated PEDOT:PSS films on PDMS substrates with random micro ridges can be potentially useful in versatile applications like stretchable conductors, thermal actuators, thermoelectric generators, and as heating surfaces. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41235.